Перспективи та ефективність зведення будівель за збірно-монолітною технологією - Тонкачеєв, Г. М. (Ways to Improve Construction Efficiency, 2013)
Perspectives of precast-monolithic construction technology and wall frame buildings. Characterized by efficiency technology and design and technology solutions. Are some examples.